Diagnosis and treatment of isolated celiac artery dissection following blunt trauma: A case report. (December 2021) - Ishimine, Tohru; Ishigami, Takahiro; Chida, Kohei; Kawasaki, Kyohei; Taniguchi, Naoki; Tengan, Toshiho
Abstract: Introduction: Celiac artery (CA) dissection due to blunt abdominal trauma is extremely rare and, as such, the clinical features of this potentially life-threatening injury have not been clearly defined, nor have treatment strategies been established. Presentation of case: We describe the case of a 61-year-old man who presented to our emergency department after a motor vehicle accident. Although the patient did not report abdominal pain, enhanced computed tomography (CT) revealed CA dissection. The patient was treated conservatively using antiplatelet therapy and was discharged from the hospital on day 8, without complications. Discussion: As abdominal pain is not a common presenting factor of CA dissection after blunt trauma, it should be suspected as a potential injury in all affected patients and comprehensively assessed, with CT being the most useful diagnostic modality. Conclusion: In the absence of any signs of organ ischemia, changes in the CA aneurysm, and persistent, severe abdominal pain following blunt abdominal trauma, conservative treatment is indicated, with or without anticoagulation or antiplatelet therapy. Highlights: Celiac artery (CA) dissection due to blunt abdominal trauma is extremely rare. We describe a case of CA dissection after a motor vehicle accident. Enhanced computed tomography revealed the CA dissection. The patient was treated conservatively and was discharged from hospital on day 8.